DRASTICAI, a new index for groundwater vulnerability assessment – a Portuguese case study - Albuquerque, Teresa (2021)
Groundwater vulnerability assessment has become a useful tool for groundwater pollution pre-vention. Groundwater vulnerability maps provide useful data for protecting groundwater re-sources. Identification of agricultural patterns is an important issue for optimized land man-agement. The watershed of the Tagus River is the backbone of this study. Naturtejo UNESCO Global Geopark, in the central interior of Portugal, corresponds to a rural area. Intensive agri-cultural practices showed an increasing trend in the last decades. The most used method inter-nationally to assess vulnerability is the DRASTIC index. In this study, the DRASTICAI index is introduced. A new attribute - Anthropogenic Influence - is added here. Five levels of increasing vulnerability, from low to high, can be recognized here. The municipality of Idanha-a-Nova is most affected by intensive agricultural activities. A robust assessment of groundwater quality has a key role. Climate change scenarios and water scarcity are important issues in the coming years and particularly in the studied area. Therefore, optimized groundwater management is essential to consider in policy making strategies.